Trends in Parents' Time Investment at Children's Schools During a Period of Economic Change - Ariel Kalil; Samantha Steimle; Rebecca M. Ryan (SAGE Publishing, 2023)
This paper examines changes from 1996-2019 in U.S. parents' time investment at their children's schools using data from the National Household Education Survey (N ≈ 116,000). The most common way parents spend time at their child's school is by attending a general school meeting, which rose from 76% to 85% over this period. The proportion who volunteered at school rose slightly over time (36% to 38%), whereas the frequency of participating in school activities decreased slightly. Little change emerged in the proportion who attend a PTA/PTO meeting (~50%), whereas the proportion who spent time fundraising decreased (60% to 54%). Differences in time investment between high- versus low-income parents either narrowed significantly (attended school meetings, frequency of participation) or remained stable (attended PTO/PTA meeting, volunteered) over time, except for income-based differences in time spent fundraising for their child's school, which grew significantly. We discuss factors possibly related to these narrowing and persistent gaps.